2022
DOI: 10.1093/bib/bbac408
|View full text |Cite
|
Sign up to set email alerts
|

FP-GNN: a versatile deep learning architecture for enhanced molecular property prediction

Abstract: Accurate prediction of molecular properties, such as physicochemical and bioactive properties, as well as ADME/T (absorption, distribution, metabolism, excretion and toxicity) properties, remains a fundamental challenge for molecular design, especially for drug design and discovery. In this study, we advanced a novel deep learning architecture, termed FP-GNN (fingerprints and graph neural networks), which combined and simultaneously learned information from molecular graphs and fingerprints for molecular prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 55 publications
0
33
0
Order By: Relevance
“…FP-GNN, a new DL architecture created in our Lab, can operate over a hybrid molecular representation of molecular graphs and fingerprints to enhance molecular property prediction ( Cai et al, 2022 ). However, there may be correlations between subtasks of datasets in the field of drug discovery and development, such as PARP subtypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FP-GNN, a new DL architecture created in our Lab, can operate over a hybrid molecular representation of molecular graphs and fingerprints to enhance molecular property prediction ( Cai et al, 2022 ). However, there may be correlations between subtasks of datasets in the field of drug discovery and development, such as PARP subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…FP-GNN finally uses fully convolutional networks (FCN) to fuse the features from both GNN and FPN, and then outputs the prediction results of molecular properties. FP-GNN DL algorithm achieves state-of-the-art (SOTA) performance on multiple molecular property prediction tasks ( Cai et al, 2022 ), and is freely available at ( https://github.com/idrugLab/FP-GNN ). However, most datasets in drug discovery have substantial connections between subtasks.…”
Section: Methodsmentioning
confidence: 99%
“…FP‐GNN is a novel DL architecture for molecular property prediction, which combined and simultaneously studied the information from molecular graphs and molecular fingerprints 52–54 . The evaluation outcomes illustrated that FP‐GNN was a competitive DL algorithm for the molecular property prediction tasks.…”
Section: Methodsmentioning
confidence: 99%
“…FP-GNN is a novel DL architecture for molecular property prediction, which combined and simultaneously studied the information from molecular graphs and molecular fingerprints. [52][53][54] The evaluation outcomes illustrated that FP-GNN was a competitive DL algorithm for the molecular property prediction tasks. To achieve the best FP-GNN model, six hyperparameters are chosen to optimize by using the Hyperopt Pythonpackage 55 : the dropout rate of GAN, the number of multihead attentions, the hidden size of attentions, the hidden size and dropout rate of FPN, and the ratio of GNN in FP-GNN.…”
Section: Algorithms and Model Constructionmentioning
confidence: 99%
“…Whether utilizing convolutional neural networks (CNNs) to process regular compound image information or leveraging recurrent neural networks (RNNs) and transformer architectures to operate on semantic molecular notations like SMILES, existing studies showed that these DL networks have led to tremendous advances in cheminformatics and computational chemistry, as well as drug design and discovery. Additionally, excellent works for predicting the properties of compounds by processing the raw graph information emerged more than two decades ago. Recently, graph-based molecular representation learning methods have shown comparable capabilities compared to other molecular representations (i.e., molecular descriptors and fingerprints) due to the superior capabilities of graph neural networks (GNNs) to model graph-structured data.…”
Section: Introductionmentioning
confidence: 99%